Additive‐free Semihydrogenation of an Alkynyl Group to an Alkenyl Group over Pd−TiO2 Photocatalyst Utilizing Temporary In‐situ Deactivation. Issue 16 (11th July 2018) - Kojima, Yasumi; Fukui, Makoto; Tanaka, Atsuhiro; Hashimoto, Keiji; Kominami, Hiroshi
Abstract: Lindlar's catalyst, i. e., calcium carbonate‐supported palladium (Pd) modified with lead, has been used for semihydrogenation of an alkynyl group in the presence of hydrogen gas (H2 ). We examined hydrogenation of an alkynyl group in organosilane and hydrocarbon in methanolic suspensions of a Pd‐loaded titanium(IV) oxide (Pd−TiO2 ) photocatalyst without the use of additives and H2 . In the photocatalytic reaction, Pd particles worked as co‐catalysts for hydrogenation and alkyne hydrogenation had priority to alkene hydrogenation. Since the Pd co‐catalyst was temporarily deactivated during the reaction owing to accumulation of the oxidized product(s) of methanol, the capacity of hydrogenation of the unsaturated C−C bond was limited. By optimizing the capacity and amount of alkynes, almost complete semihydrogenation of alkynes was achieved under a poison‐free condition. Pd−TiO2 can be regenerated by very simple treatments, i. e., washing and drying at room temperature. Abstract : Additive‐free : Alkyne hydrogenation had priority to alkene hydrogenation over Pd−TiO2 photocatalyst and the Pd co‐catalyst was temporarily deactivated during the reaction, resulting in almost complete semihydrogenation of alkynes by optimizing the amount of alkynes under an additive‐free condition.